2014
DOI: 10.1017/s000748531300062x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and insecticide resistance during the growing season in the green peach aphid (Hemiptera: Aphididae) on primary and secondary hosts: a farm-scale study in Central Chile

Abstract: The seasonal dynamics of neutral genetic diversity and the insecticide resistance mechanisms of insect pests at the farm scale are still poorly documented. Here this was addressed in the green peach aphid Myzus persicae (Sulzer) (Hemiptera: Aphididae) in Central Chile. Samples were collected from an insecticide sprayed peach (Prunus persica L.) orchard (primary host), and a sweet-pepper (Capsicum annum var. grossum L.) field (secondary host). In addition, aphids from weeds (secondary hosts) growing among these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 67 publications
3
16
0
Order By: Relevance
“…Regarding the MACE mutation, a high frequency of the SS genotype was detected (SS > RS > RR) in our study. A similar situation has been detected in the UK 27 and Chile, although in samples collected with suction traps (regional scale) and from peach trees and sweet‐pepper hosts (farm scale), respectively. Studies from the UK 19 and Tunisia have reported a wide range in the frequency of SS genotypes (ranging between 15 and 100% in samples collected from peach trees, potato, brassica, and tobacco).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Regarding the MACE mutation, a high frequency of the SS genotype was detected (SS > RS > RR) in our study. A similar situation has been detected in the UK 27 and Chile, although in samples collected with suction traps (regional scale) and from peach trees and sweet‐pepper hosts (farm scale), respectively. Studies from the UK 19 and Tunisia have reported a wide range in the frequency of SS genotypes (ranging between 15 and 100% in samples collected from peach trees, potato, brassica, and tobacco).…”
Section: Discussionsupporting
confidence: 74%
“…Regarding super ‐kdr , this mutation exhibited a very low frequency of RR and RS genotypes, with the following frequency order: SS > RS > RR (Table ). In our study, we report for the first time in Chile the presence of a resistant homozygote genotype . This genotype was detected in the spring of the last year studied (2012), mainly in the TM and VH orchards.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…To date 135 aphid species have been reported, 104 of them introduced, and most constitute economically important pests (Zepeda-Paulo et al, 2010). Overall, little is known about their biology, and even less about the factors determining their introduction process and underlying causes of success, although some research has been done in the case of the grain aphid Sitobion avenae, the pea aphid A. pisum and the tobacco aphid, M. persicae nicotianae (Figueroa et al, 2005;Peccoud et al, 2008;Zepeda-Paulo et al, 2010;Rubiano-Rodriguez et al, 2014). Populations of those species are characterized in Chile by a few common genotypes, usually predominant and time-persistent, usually referred as "superclones" (Vorburger et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The species is considered to be anholocyclic in other areas [ 1 , 14 ]. Similarly, green peach aphid populations are also genetically more diverse in areas where sexual reproduction occurs than in areas where asexual reproduction predominates [ 23 ]. Pairwise F ST values indicated there were moderate levels of genetic differentiation among geographic and Anyang populations.…”
Section: Discussionmentioning
confidence: 99%